Workplace Digital Strategies and Managerial Success - Simon Emmanuel Hart (Journal of Advanced Research in Entrepreneurship, Innovation and SMES Management, 2024)
This paper aims to unravel the interconnectivity between workplace digital strategies and managerial success, meanwhile, it was the objective of this study to identify the extent of the relationship between use of computers and managerial effectiveness; and use of internet services and managerial productivity. The study adopted the descriptive survey research design. Data regarding the population of this study was obtained from the Oil and Gas Services Head offices in Port Harcourt. However, 10 top managers and 22 staff comprises the study sample. Hence, the study adopted a purposive sampling technique. To acquire primary data, a structured questionnaire entitled “Workplace Digital Strategies and Managerial Success Index (WDSMSI)” was designed on a four-point Likert scale. The data obtained from the field were analyzed using Spearman’s Rank Order Correlation Coefficient with the aid of SPSS 22.0. The test of hypothesis one revealed a significantly strong relationship between the use of computers and managerial efficiency. The test of hypothesis two showed a significant strong relationship between the use of internet and the managerial productivity of oil and gas companies. Based on the findings and conclusion, it was recommended among others that managers should utilize the latest digital technologies latest i3 computers, which are highly rated in management digital information processing. Management should also enable digital applications for both employees and company clients to carry out virtual operations, so as to promote customer satisfaction.